Clinical outcomes and complications of four surgical techniques for tibial avulsion fractures of the posterior cruciate ligament: a retrospective comparative study - Zhenghui Hu; Yanze Xia; Chang She; Liubing Li; Wei Xu (Journal of Orthopaedic Surgery and Research)
Abstract Objective The optimal surgical approach for tibial avulsion fractures of the posterior cruciate ligament (PCL) remains controversial. This study aimed to compare the clinical outcomes of four techniques: arthroscopic suture fixation, arthroscopic loop plate fixation, open reduction with cannulated screw fixation, and open reduction with anchor suture bridge fixation. Methods A retrospective review was conducted of 73 patients treated between January 2019 and December 2023 using one of four surgical techniques: arthroscopic suture fixation (Group A, n = 26), arthroscopic loop plate fixation (Group B, n = 14), open reduction with cannulated screw fixation (Group C, n = 16), and open reduction with anchor suture bridge fixation (Group D, n = 17). Demographic data, operative time, pre- and postoperative visual analog scale (VAS) pain scores, Lysholm scores, International Knee Documentation Committee (IKDC) scores, knee range of motion (ROM), and postoperative complications were analyzed. Results No significant differences were observed in baseline demographic data among the four groups (P >.05). Operative time was shortest in Group D (60.41 ± 12.39 min), significantly less than in the other groups (P =.0001). At 3 months postoperatively, all groups demonstrated significant improvements in VAS, Lysholm, and IKDC scores (P <.0001); however, intergroup differences were not statistically significant (P >.05). Group A demonstrated significantly less ROM recovery compared with the other groups (P =.0171). At final follow-up, further improvements in functional scores and ROM were observed in all groups, with no significant intergroup differences (P >.05). Complication rates differed significantly among the groups (P =.0361), with Group D reporting the lowest rate (0%) and Group A the highest (34.6%). Conclusion No significant differences were found in overall clinical outcomes among the four techniques. However, open reduction with anchor suture bridge fixation demonstrated favorable operative efficiency and complication profile, suggesting clinical advantages in selected patients. Trial registration Chinese Clinical Trial Registry: ChiCTR2500100641. Registration Date: 2025-04-11, Retrospectively registered.